2019
DOI: 10.1177/0091217419860716
|View full text |Cite
|
Sign up to set email alerts
|

Updates in insomnia diagnosis and treatment

Abstract: Introduction Insomnia is the most commonly reported sleep disorder and remains undertreated in many patients. New changes to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, have changed the way insomnia is diagnosed. In patients who suffer from insomnia, a number of available treatment options exist including both behavioral therapy and medications. Literature Review: First line therapy for insomnia should always include behavioral modifications such as sleep hygiene and insomnia-orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 20 publications
0
35
0
2
Order By: Relevance
“…In addition, it is essential for those with chronic insomnia to maintain a consistent sleep-wake cycle with circumvention of daytime napping; this is referred to as temporal control therapy. 9,11 Stimulus control therapy can be used to help the patient associate the bedroom with sleep and is characterized by lying down only when ready to sleep, getting out of bed after 20 minutes of lying down if unable to fall asleep, using the bed strictly for sleep and sex, and waking at a similar time each day regardless of the time of sleep onset. Patients without a history of bipolar disorder or epilepsy who spend prolonged times in bed trying to fall asleep may benefit from sleep restriction therapy (minimum of five hours) until homeostatic sleep drive increases and improve sleep efficiency.…”
Section: Current Treatment Of Insomnia Initial Non-pharmacologic Approachesmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, it is essential for those with chronic insomnia to maintain a consistent sleep-wake cycle with circumvention of daytime napping; this is referred to as temporal control therapy. 9,11 Stimulus control therapy can be used to help the patient associate the bedroom with sleep and is characterized by lying down only when ready to sleep, getting out of bed after 20 minutes of lying down if unable to fall asleep, using the bed strictly for sleep and sex, and waking at a similar time each day regardless of the time of sleep onset. Patients without a history of bipolar disorder or epilepsy who spend prolonged times in bed trying to fall asleep may benefit from sleep restriction therapy (minimum of five hours) until homeostatic sleep drive increases and improve sleep efficiency.…”
Section: Current Treatment Of Insomnia Initial Non-pharmacologic Approachesmentioning
confidence: 99%
“…RCTs have demonstrated that these drugs significantly decreased sleep latency compared to placebo by an average of 20 minutes (P<0.0001) and sustained those results long-term. 11,19 Zolpidem immediate release is superior at reducing sleep latency and increasing TST out of all the z-drugs, making it a frequent first choice medication in this group. Zolpidem extended-release does not offer any additional benefit for treating insomnia but may increase the risk of next-day impairment.…”
Section: Non-benzodiazepine Hypnoticsmentioning
confidence: 99%
See 3 more Smart Citations